Colorectal polypectomy and endoscopic mucosal resection: European Society of Gastrointestinal Endoscopy (ESGE) Guideline – Update 2024 - Ferlitsch, Monika; Hassan, Cesare; Bisschops, Raf; Bhandari, Pradeep; Dinis-Ribeiro, Mário; Risio, Mauro; Paspatis, Gregorios A.; Moss, Alan; Libânio, Diogo; Lorenzo-Zúñiga, Vincente; Voiosu, Andrei M.; Rutter, Matthew D.; Pellisé, Maria; Moons, Leon M. G.; Probst, Andreas; Awadie, Halim; Amato, Arnaldo; Takeuchi, Yoji; Repici, Alessandro; Rahmi, Gabriel; Koecklin, Hugo U.; Albéniz, Eduardo; Rockenbauer, Lisa-Maria; Waldmann, Elisabeth; Messmann, Helmut; Triantafyllou, Konstantinos; Jover, Rodrigo; Gralnek, Ian M.; Dekker, Evelien; Bourke, Michael J. (Endoscopy, 2024)
1 ESGE recommends cold snare polypectomy (CSP), to include a clear margin of normal tissue (1–2 mm) surrounding the polyp, for the removal of diminutive polyps (≤ 5 mm).Strong recommendation, high quality of evidence.2 ESGE recommends against the use of cold biopsy forceps excision because of its high rate of incomplete resection.Strong recommendation, moderate quality of evidence.3 ESGE recommends CSP, to include a clear margin of normal tissue (1–2 mm) surrounding the polyp, for the removal of small polyps (6–9 mm).Strong recommendation, high quality of evidence.4 ESGE recommends hot snare polypectomy for the removal of nonpedunculated adenomatous polyps of 10–19 mm in size.Strong recommendation, high quality of evidence.5 ESGE recommends conventional (diathermy-based) endoscopic mucosal resection (EMR) for large (≥ 20 mm) nonpedunculated adenomatous polyps (LNPCPs).Strong recommendation, high quality of evidence.6 ESGE suggests that underwater EMR can be considered an alternative to conventional hot EMR for the treatment of adenomatous LNPCPs.Weak recommendation, moderate quality of evidence.7 Endoscopic submucosal dissection (ESD) may also be suggested as an alternative for removal of LNPCPs of ≥ 20 mm in selected cases and in high-volume centers.Weak recommendation, low quality evidence.8 ESGE recommends that, after piecemeal EMR of LNPCPs by hot snare, the resection margins should be treated by thermal ablation using snare-tip soft coagulation to prevent adenoma recurrence.Strong recommendation, high quality of evidence.9 ESGE recommends (piecemeal) cold snare polypectomy or cold EMR for SSLs of all sizes without suspected dysplasia.Strong recommendation, moderate quality of evidence.10 ESGE recommends prophylactic endoscopic clip closure of the mucosal defect after EMR of LNPCPs in the right colon to reduce to reduce the risk of delayed bleeding.Strong recommendation, high quality of evidence.11 ESGE recommends that en bloc resection techniques, such as en bloc EMR, ESD, endoscopic intermuscular dissection, endoscopic full-thickness resection, or surgery should be the techniques of choice in cases with suspected superficial invasive carcinoma, which otherwise cannot be removed en bloc by standard polypectomy or EMR.Strong recommendation, moderate quality of evidence.